Assessment of Hematological Changes in COVID-19: An Update - Das , Subhashis; Nikhil; Khichariya , Gaurav; Amrutha , T.; Sinha , Snigdha (New Advances in Medicine and Medical Science Vol. 2, 2023)
The aim of the study is to assess hematological changes in COVID-19 Subjects and compare the leukocyte variation between ICU and Non-ICU group. Haematological changes have been demonstrated in COVID-19 patients COVID-19 subjects shows varying degrees of leukopenia and lymphopenia. Haematological changes in COVID-19 helps in predicting severity and prognosis of the disease. Published literature advocates that neutrophilia, lymphopenia are prognostic parameters as they are generally observed in severe cases. Combination of haematological parameters such as neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) is increased in COVID-19 subjects as compared to healthy controls in studies done by et al studies. Identical results were obtained in current study There is shortage of data with respect to role of eosinophils in COVID-19. It is observed that eosinopenia is noted is associated with severe COVID-19 disease. In Current research we observed the haematological profile in COVID-9 subjects and correlated with severity and prognosis of the disease. Predicting the severity and prognosis can help in treating at the earliest and will prevent further progression of the disease.